Evaluasi Kinerja Guru Bersertifikasi Dengan Model Charlotte Danielson - Oktriany, Wara Hapsari; Sulasmono, Bambang Suteng; Iriani, Ade (Universitas Kristen Satya Wacana, 2018)
This study aims to evaluate the performance of certified teachers in SMP Negeri 3 Salatiga in the domain: (1) planning and preparation of learning, (2) class management, (3) learning process, and (4) professional teacher responsibility. This research is an evaluative research using Charlotte Danielson Model, with simple qualitative and quantitative method. The subjects were five teachers of SMP Negeri 3 Salatiga who have been certified educators. Data collection through interviews, observation, and document study. Moderate data collection instruments include teacher performance assessment rubric, interview guides, and questionnaires. The data validity test is done by source and technique triangulation. The results of this study: (1) the certified teacher performance in preparing and planning of learning is included in the good category, (2) the certified teacher performance in managing the classes included in the good category; (3) the certified teacher performance in the learning process included in either category, and (4) the certified teacher performance in their professional responsibilities is categorized as good enough, due to the lack of teachers efforts to develop themselves.